Assessment of repeat target lesion percutaneous coronary intervention as a quality measure for public reporting and general quality assessment for PCIs. Issue 4 (23rd October 2019) - Hannan, Edward L.; Zhong, Ye; Ling, Frederick S. K.; Tamis‐Holland, Jacqueline; Berger, Peter B.; Jacobs, Alice K.; Walford, Gary; Venditti, Ferdinand J.; King, Spencer B.
Abstract: Background: Target lesion percutaneous coronary intervention (TLPCI) within 1 year of PCI has been proposed by critics of public reporting of short‐term mortality as an alternative measure for PCI reporting. Methods: New York's PCI registry was used to identify 1‐year repeat TLPCI and 1‐year repeat TLPCI/mortality for patients discharged between December 1, 2013 and November 30, 2014. Significant independent predictors of the outcomes were identified. Hospital and cardiologist risk‐adjusted outcomes were calculated, and outlier status and correlations of risk‐adjusted rates were examined for the three outcomes. Results: The adverse outcome rates were 1.30, 4.21, and 8.97% for in‐hospital/30‐day mortality, 1‐year repeat TLPCI, and 1‐year repeat TLPCI/mortality. There were many commonalities but also many differences in significant predictors of the outcomes. Hospital and cardiologist risk‐adjusted 1‐year repeat TLPCI rates and repeat TLPCI/mortality rates were poorly correlated with risk‐adjusted in‐hospital/30‐day mortality rates (eg, Spearman R = −.16 [ p = .23] and .27 [ p = .04], respectively, for hospital 1‐year repeat TLPCI vs. in‐hospital/30‐day mortality). Many more providers were found to have significantly higher and lower rates for repeat TLPCI than for short‐term mortality. Conclusions: Hospital and cardiologist quality assessments are very different for TLPCI and repeat TLPCI/mortality than they are for short‐term mortality. Repeat TLPCI/mortality rates are highly correlated with repeat TLPCI rates, but outlier providers differ. More study of repeat TLPCI and all the patient, cardiologist, and hospital factors associated with it may be required before using it as a supplement to, or in lieu of, short‐term mortality in public reporting of PCI outcomes.